Too close for cycling comfort? Social and physical contributors to subjective cycling safety in the context of overtaking: Results from a mixed-methods study combining data from OpenBikeSensors, the SimRa app, and qualitative interviews - Jennifer Bosen; Annika Herberg; Carmella Pfaffenbach; Carmen Leicht-Scholten (Journal of Urban Mobility)
Cycling is a central component of the mobility transition towards a sustainable mobility culture. While existing research on cycling largely focuses on transport infrastructure, the influence of subjective safety as a key factor in the decision to cycle remains understudied.This study contributes to the growing body of research on subjective safety in cycling, presenting findings from an explorative, mixed-methods, inter- and transdisciplinary examination of subjective safety in the context of overtaking of cyclists in Aachen, Germany. Ten participants (gender-balanced, non-disabled, white, German, with a mix of ages, household sizes, and care responsibilities), were equipped with OpenBikeSensors (OBS) and the SimRa (German acronym for ‘safety in bicycle traffic’) app to measure overtaking distances and track incidents such as near misses. The individual OBS and SimRa data maps were then used as prompts in problem-centred qualitative interviews, which were analysed following qualitative content analysis and contextualised with the OBS and SimRa data.Results show that factors contributing to subjective cycling safety are highly individualised and multifaceted. Beyond physical vulnerability, subjective cycling safety includes factors of social vulnerability. The mitigation of factors contributing to subjective safety can be a route to cycling resilience and cycling agency. Planning for a cycling-friendly mobility culture requires addressing aspects related to transport equity and inclusion, particularly in relation to social vulnerability, in order to improve subjective cycling safety. Inter- and transdisciplinary collaborations, and mixed-method analyses, can generate scientific results to support and inform policy and practice, ultimately increasing the relevance of research results for sustainable transport planning.